If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(7r + -1) = -8 + 2r Reorder the terms: 8(-1 + 7r) = -8 + 2r (-1 * 8 + 7r * 8) = -8 + 2r (-8 + 56r) = -8 + 2r Add '8' to each side of the equation. -8 + 8 + 56r = -8 + 8 + 2r Combine like terms: -8 + 8 = 0 0 + 56r = -8 + 8 + 2r 56r = -8 + 8 + 2r Combine like terms: -8 + 8 = 0 56r = 0 + 2r 56r = 2r Solving 56r = 2r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-2r' to each side of the equation. 56r + -2r = 2r + -2r Combine like terms: 56r + -2r = 54r 54r = 2r + -2r Combine like terms: 2r + -2r = 0 54r = 0 Divide each side by '54'. r = 0 Simplifying r = 0
| 8(-8+4x)=-36+4x | | 8(-8+4x)=36+4x | | 2(4-4n)=-6+6n | | 9x+13=11x | | 17x+108=y | | 8w-11=69 | | 16=-16x^2+36 | | 10=-16x^2+46 | | x/(1-x)=1.44 | | F(x)=x^100-1 | | 2m=11-3m | | r^3+3r-10=0 | | 6x^2+3x-c=0 | | lg*(x-2)+lg*(x+3)=lg*14 | | (x+3i)(y-2i)=18+6i | | 11r+1=5r+19 | | 6m-12=2m+8 | | 5y-27=3y-5 | | x^2+(k-2)x+(k+3)=0 | | (7+w)(5w-2)=0 | | 2e^2x-3=4equation | | 5x^2-29x-9= | | 80=4x+2y | | -0.5x^2+36x-310=0 | | 0.5x^2+36x-310=0 | | 8-4w=2w+5 | | =3-6x-3x^2 | | 3(6x-6)=-144 | | G(x)=60-3-2x | | 4(10-x)=24 | | G(x)=60-2x | | 8(x+3)=6(x-7) |